2012
DOI: 10.1080/03079457.2012.718070
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology ofEnterococcus cecorumisolates recovered from enterococcal spondylitis outbreaks in the southeastern United States

Abstract: Enterococcus cecorum, a normal intestinal inhabitant, is increasingly responsible for outbreaks of arthritis and osteomyelitis in chickens worldwide. Enterococcal spondylitis (ES) is a specific manifestation of E. cecorum-associated disease in which increased flock morbidity and mortality result from chronic infection involving the free thoracic vertebra. In this study the genetic relatedness and antimicrobial resistance of isolates recovered from ES-affected flocks in the southeastern United States were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 15 publications
7
75
1
Order By: Relevance
“…cecorum from clinical and nonclinical birds has not been previously described, antimicrobial resistance results from other studies indicated that the use of antimicrobials in poultry may have selected for isolates that are resistant to a broader range of antimicrobials than the nonpathogenic isolates and those strains may also harbour more resistance genes (Borst et al . ). This was not evident in this study as no significant difference in MDR between Ent.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…cecorum from clinical and nonclinical birds has not been previously described, antimicrobial resistance results from other studies indicated that the use of antimicrobials in poultry may have selected for isolates that are resistant to a broader range of antimicrobials than the nonpathogenic isolates and those strains may also harbour more resistance genes (Borst et al . ). This was not evident in this study as no significant difference in MDR between Ent.…”
Section: Resultsmentioning
confidence: 97%
“…; Borst et al . ; Wijetunge et al . ), cross‐clustering of some of the isolates in this study suggests that there are shared genetic attributes among some of the isolates and not all isolates can be distinguished as clinical and nonclinical based on this method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both pathogenic and commensal EC demonstrated decreased susceptibility to multiple antimicrobials, including enrofloxacin, novobiocin, spectinomycin, streptomycin, sulfathiazole, sulfadimethoxine and tylosin tartrate (Borst et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Enterococci are normal inhabitants of the intestinal flora of poultry, but are increasingly recognised as causing a range of diseases, such as those described in this case. The possibility has been reported of spinal lesions being associated with newly emerging clones of E cecorum with increased pathogenicity (Borst and others 2012). …”
Section: Highlights From the Scanning Surveillance Networkmentioning
confidence: 99%